2006
DOI: 10.1080/10610270500450739
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three computer office workstations offering forearm support: impact on upper limb posture and muscle activation

Abstract: The aims of the study were: 1) to determine whether resting the forearms on the work surface, as compared to chair armrests, reduces muscular activation; 2) to compare the sensitivity of different electromyographic (EMG) summary parameters. Eighteen healthy subjects performed computer work (with keyboard and mouse alternately) for 20 min while resting their forearms on a work surface adjustable in height (Workstation A), on the chair's armrests with an adjustable workstation (Workstation B) or on their chair's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 42 publications
2
40
1
6
Order By: Relevance
“…[ research report ] the supraspinatus, which is the muscle most commonly involved in rotator cuff tears. 7,11,12,40,46 Kelly et al 23 investigated EMG data for more intense ADLs, such as lifting 1-to 10-pound (0.5-to 4.5-kg) objects and washing the back, in subjects with symptomatic versus asymptomatic rotator cuff tears compared to healthy controls. The results of that study showed that the symptomatic patients had more EMG signal amplitude for the muscles of the torn rotator cuff tendon than the asymptomatic patients, which could explain the disability of the symptomatic patients who were not compensating by using the surrounding shoulder musculature.…”
Section: Results Tmentioning
confidence: 99%
“…[ research report ] the supraspinatus, which is the muscle most commonly involved in rotator cuff tears. 7,11,12,40,46 Kelly et al 23 investigated EMG data for more intense ADLs, such as lifting 1-to 10-pound (0.5-to 4.5-kg) objects and washing the back, in subjects with symptomatic versus asymptomatic rotator cuff tears compared to healthy controls. The results of that study showed that the symptomatic patients had more EMG signal amplitude for the muscles of the torn rotator cuff tendon than the asymptomatic patients, which could explain the disability of the symptomatic patients who were not compensating by using the surrounding shoulder musculature.…”
Section: Results Tmentioning
confidence: 99%
“…A recent study by Delisle et al (2006) highlights the value of considering exposure variability. This study compared support from chair armrests (with and without the use of an adjustable workstation) and support from the desk surface during computer work.…”
Section: Introductionmentioning
confidence: 97%
“…Supporting the forearm during computer work has been previously recommended as it promotes stability of the upper body with less strain on thoracic muscles such as trapezius, deltoid, and extensor digitorum (recorded using electromyography) (Delisle et al, 2006;Karlqvist, 1998;Nevala-Puranen et al, 2003;Saarni et al, 2007). However, in terms of postural benefit, the findings of this study support the previous literature in that forearm supported posture potentially promotes a more stooped head and shoulder posture (Bendix et al, 1985;Zacharkow, 1988).…”
Section: Discussionsupporting
confidence: 47%
“…This is somewhat in contrast to Chapter 6, where cultural differences in depression and anxiety symptoms appeared to be explained by other factors such as job strain and coping resources. These contrasting findings overall suggest that future studies will need to consider the potential effect of cultural differences when making inferences about findings observed in just one culture.Several ergonomic factors impacted on the maintenance of neutral posture in office workers.Interestingly the majority of participants (67.9%) in this study postured their forearms such that they were supported on the desk top while working with the mouse or keyboard.Supporting the forearm during computer work has been previously recommended as it promotes stability of the upper body with less strain on thoracic muscles such as trapezius, deltoid, and extensor digitorum (recorded using electromyography) (Delisle et al, 2006;Karlqvist, 1998;Nevala-Puranen et al, 2003;Saarni et al, 2007). However, in terms of postural benefit, the findings of this study support the previous literature in that forearm supported posture potentially promotes a more stooped head and shoulder posture (Bendix et al, 1985;Zacharkow, 1988).…”
supporting
confidence: 47%